Face Threatening Acts In Jeong Myeong-Seok Documentary (2023) - Frisca FIfian; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
This journal article examines the speech acts within the Jeong Myeong-Seok cult, as portrayed in the documentary In the Name of God: Unholy Betrayal (2023). Through a pragmatic lens, the study investigates the use of face-threatening acts (FTAs) and politeness strategies in Jeong Myeong-Seok's manipulation of followers through verbal communication. The analysis focuses on the contextual significance of Jeong Myeong-Seok's language, considering both the intended meaning of the speaker and the interpretation by listeners. The concept of face, encompassing positive and negative faces, is employed to understand how FTAs jeopardize the self-perception and social identity of the interlocutors. Employing a descriptive, qualitative research methodology, the study presents findings and discussions derived from data extracted from the documentary, shedding light on the specific FTAs employed by Jeong Myeong-Seok and the corresponding use of politeness strategies. The research aims to enhance comprehension of power dynamics in cults and the significant role played by language in manipulating the beliefs and actions of followers. This study contributes to the advancement of knowledge in the fields of education, language, and literature by providing insights into the intricate relationship between language use, power dynamics, and influence within cults, thereby enriching the scholarly discourse in these domains.